Intelligent material and preparation method and application thereof

By introducing low-melting point alloy particles and carbon nanotubes or graphene into smart materials, the problems of insufficient stiffness and strength and lack of sensing functions of existing smart materials are solved, and the high stiffness, high strength and excellent sensing performance of the material are achieved.

CN119798997AInactive Publication Date: 2025-04-11NINGBO NOTTINGHAM CHINA BEACONS OF EXCELLENCE RES & INNOVATION INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411506536.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing smart materials have shortcomings in bearing and transmitting stress, and cannot effectively improve the stiffness and strength of composite materials, and at the same time lack sensing functions.

Method used

Low-melting point alloy particles, carbon nanotubes or graphene are used as functional fillers to disperse uniformly in the elastomer prepolymer to form smart materials. By regulating the composition and particle melting point of low-melting alloys, the mechanical properties of the elastomer are customized, and the sensing function is introduced through carbon nanotubes or graphene.

Benefits of technology

The stiffness and strength of the composite material are significantly improved and the material is given a sensing function, allowing it to produce a significant electrical signal response when external stress, temperature or other environmental changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798997A_ABST
    Figure CN119798997A_ABST
Patent Text Reader

Abstract

The invention relates to an intelligent material and a preparation method and application thereof, and is characterized in that the main components of the material comprise 20-40% of a dispersion phase, 50-70% of a dispersion medium and 1-6% of a functional filler based on the total volume of the material, the dispersion phase and the functional material are uniformly dispersed in the dispersion medium, the dispersion phase comprises low-melting-point alloy particles, and the functional filler comprises a high-melting-point alloy particle and a low-melting-point alloy particle. The dispersion medium comprises an elastomer prepolymer; the functional filler is a carbon nano tube or graphene; according to the technical scheme, the composite material has the advantages that stress can be effectively borne and transmitted, so that the rigidity and strength of the composite material are improved, and the sensing function is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular, to preparing smart materials by dispersing low melting point alloy (LPMA) micron-sized particles with different melting points and functional fillers in a dispersion medium, and to specific applications of the materials. Background Art

[0002] Smart materials (also called responsive materials) are materials that have one or more properties through design, can sense external stimuli, gradually eliminate the boundary between functional materials and structural materials in the traditional sense, and realize structural functionalization and functional diversification. Generally speaking, smart materials have seven functions, namely sensing function, feedback function, information recognition and accumulation function, response function, self-diagnosis ability, self-repair ability and self-adaptation ability.

[0003] Smart materials need to have the following characteristics:

[0004] 1. It has the function of sensing, detecting and identifying the intensity of external or internal stimuli, such as electricity, light, heat, stress, strain, chemistry, etc.;

[0005] 2. It has driving function according to the changes in the external environment;

[0006] 3. The response can be selected and controlled in a designed way;

[0007] 4. Responsive, timely and accurate;

[0008] 4. After the external factors are eliminated, it can quickly return to its original state;

[0009] Low melting point alloys are composed of low melting point metal elements such as lead, cadmium, tin, antimony, tin, indium, and bismuth. Their melting point is generally between 60 and 200 °C and they are very sensitive to temperature changes. When foreign atoms enter the crystal, the metal bonds are destroyed, the metal becomes chaotically arranged, the metal's internal energy increases, and the melting point decreases. After the heat field is applied, the interaction force between the molecules of the low melting point alloy decreases, which is manifested macroscopically as melting from solid to liquid in a short time; after the heat field is removed, the liquid low melting point alloy can be transformed back to solid in a relatively short time. Low melting point alloys are a type of intelligent material with great development potential. They have a simple manufacturing process, low manufacturing cost, and sensitive reaction speed. They have a broad application background in flexible robots and soft brakes.

[0010] The patent document with publication number CN105349866A discloses a low melting point alloy with a melting point of 40 to 60°C and a preparation method thereof, wherein the components include indium, bismuth, tin, gallium and a small amount of lead or cadmium. The preparation process of this low melting point alloy is simple, and it is applied to low temperature occasions in the form of phase change. It can be synthesized in an atmospheric environment, and the production cost is low, which increases the range of liquid metal thermal interface materials. At the same time, it is solid at a lower temperature, and gradually becomes liquid as the temperature rises, and cannot be formed. The patent document with publication number CN110218329A discloses a polysiloxane controlled by temperature sensitivity and related applications. The mechanical properties of the modified material can change significantly within a certain temperature from a low temperature state to a high temperature state. Since the material can quickly switch between two stable states, the invention is particularly used to prepare temperature-sensitive rapid shaping materials, which are used for surgical medical fixation materials, correction materials, etc.

[0011] Multiphase steady-state materials are composite structures with multiple different stable states. The material has a certain load-bearing capacity in each stable state, and after being given external stimulation, the material can change between stable states. The elastic modulus of the cured material reflects the stiffness of the smart material, and the change in stiffness reflects that the smart material can be converted between multiple stable states. In addition, shear thinning, also known as pseudoplasticity, is the most common phenomenon of non-Newtonian fluids, reflecting that the viscosity of the smart material decreases with the increase of shear strain rate. For polymer systems, shear thinning is caused by the entanglement of polymer chains during flow; in static conditions, high molecular weight polymers are entangled and randomly oriented; when a sufficiently high rate of shear is given, the highly anisotropic polymer chains begin to unravel, which leads to fewer particle or molecular interactions and a large amount of free space for activity, thereby reducing viscosity. The phenomenon of viscoelastic inversion is an important parameter for judging whether smart materials can be 3D printed. As the dynamic shear stress provided increases, the changes in the elastic modulus and viscous modulus change at a certain point; at the same time, the intersection point can reflect the pressure value that needs to be given when performing 3D direct writing printing.

[0012] In addition, the applicant applied for a patent document for a smart material, its preparation method and application, which uses a mixture of multiple low-melting point alloy particles as a dispersed phase. The multiple low-melting point alloys have multiple stable states, a wide range of controllability possibilities, and a fast response speed. It also adopts a method of mixing elastomer prepolymers with low-melting point alloy particles. The resulting smart material slurry has shear thinning and viscoelastic inversion phenomena, can be used as a 3D printing material, can maintain a stable state in multiple states with good stability, excellent thermal conductivity, simple and easy preparation method, low cost, and can be used in the field of additive manufacturing. However, the smart material obtained by this application still has certain shortcomings: the material cannot effectively withstand and transmit stress, cannot improve the stiffness and strength of the composite material, and has no sensing function. Summary of the invention

[0013] In view of the above-mentioned deficiencies in the prior art, the present application provides an intelligent material that can effectively withstand and transmit stress, thereby improving the stiffness and strength of the composite material and has a sensing function.

[0014] In order to solve the above technical problems, the technical solution adopted in this application is: a smart material, the main components of which include a dispersed phase accounting for 20-40% of the total volume fraction of the material, a dispersion medium of 50-70% and a functional filler of 1-6%, the dispersed phase and the functional material are uniformly dispersed in the dispersion medium, the dispersed phase includes low melting point alloy particles, the dispersion medium includes an elastomer prepolymer; the functional filler is carbon nanotubes or graphene.

[0015] Furthermore, the main components of the material include 23-35% of the dispersed phase, 55-65% of the dispersion medium and 1-5% of the functional filler, based on the total volume of the material.

[0016] Furthermore, the low melting point alloy is a mixture of different types of low melting point alloys, specifically including one or more of Ga, Ga-In-Sn-Bi, and Ga-In-Sn-Pb; the mechanical properties of the elastomer, such as hardness, elastic modulus, and tensile strength, can be customized by using the material. This control capability enables the elastomer to meet the specific needs of different applications.

[0017] Furthermore, the melting point of the low-melting-point alloy particles is lower than 200°C.

[0018] Furthermore, the melting point of the low-melting-point alloy particles is 30-70°C.

[0019] Furthermore, the elastomer prepolymer includes any one of PDMS SE1700 (silicone rubber), PDMS (polydimethylsiloxane) 184, Ecoflex 00-30 (platinum-cured silicone), and Ecoflex 00-50, or a combination of two or more thereof.

[0020] The present application also provides a method for preparing the above-mentioned smart material, which comprises: uniformly mixing low-melting-point alloy particles, functional fillers and elastomer prepolymers to prepare smart material slurry, and then solidifying to obtain the smart material.

[0021] Furthermore, more specifically, the method for preparing the smart material comprises:

[0022] (1) providing a first mixed system comprising low melting point alloy particles, a functional filler and a first prepolymer component;

[0023] (2) Adding a second prepolymer component to the first mixed system, and then stirring and mixing to form a second mixed system, to obtain a 3D printable smart material slurry, and then curing to obtain a smart material elastomer.

[0024] Furthermore, the first prepolymer component is the elastomer prepolymer, and the second prepolymer component is the elastomer prepolymer; the present application adds the prepolymer component twice, because the first prepolymer component will be cured only by adding the second prepolymer component. If the prepolymer component is added at one time, the mixture will be cured prematurely during the first step of mixing and stirring due to the heat generated.

[0025] The present application also provides an application of the above-mentioned smart material in the field of 3D printing.

[0026] Furthermore, in the 3D printing, the temperature of the printing process is no higher than 10°C.

[0027] Furthermore, the applied products include the development of intelligent drug delivery systems, wearable medical devices and precision diagnostic tools.

[0028] Advantages and beneficial effects of this application:

[0029] 1. In the present application, by adding carbon nanotubes or graphene as functional fillers to smart materials, the stiffness of the material before addition varies from 5 to 7 MPa, while the stiffness of the material after addition varies from 9 to 18 MPa. This is because carbon nanotubes or graphene have very high Young's modulus, wherein the Young's modulus of graphene is as high as 1 TPa, and the Young's modulus of carbon nanotubes can reach 0.8 TPa. When these high modulus materials are uniformly dispersed in the elastomer matrix as functional materials, they can effectively withstand and transmit stress, thereby improving the stiffness and strength of the composite material; interfacial slip may occur between graphene or carbon nanotubes and the elastomer matrix, resulting in an increase in the stiffness change before and after the LMPA phase transition; in addition, in order to give the composite material excellent sensing function, carbon nanotubes or graphene are deliberately introduced as functional fillers in the process of preparing the prepolymer slurry. These nanoscale materials have excellent electrical conductivity and mechanical properties, which can effectively enhance the conductivity and sensitivity of the composite material, so that the material can generate obvious electrical signal response when external stress, temperature or other environmental changes occur; this design strategy not only gives the composite material sensing function, but also improves its overall performance, laying a solid foundation for the development of smart materials and structures.

[0030] 2. The carbon nanotubes or graphene used in the present application can introduce sensitivity to temperature changes in the elastomer of the present application due to its excellent sensing properties; this is because carbon nanotubes or graphene, as a two-dimensional nanomaterial with excellent performance, has a thermal conductivity of up to 3000-5000W / m·K. Introducing them into the elastomer can improve the thermal conductivity of the material and enable the elastomer to reach thermal equilibrium more quickly when the temperature changes; as the temperature rises, the interface between the carbon nanotubes or graphene and the elastomer matrix will interact, promote heat transfer, and thereby change the temperature sensitivity of the material.

[0031] 3. The LMPA (low melting point alloy) used in the present application, due to its unique low melting point characteristics, enables the elastomer to be easily reshaped and reused when heated; this characteristic greatly improves the sustainability of the material because it reduces the generation of waste materials, while also reducing production and maintenance costs, thereby improving the economic efficiency of the material; in addition, carbon nanotubes or graphene, with their excellent sensing properties, can introduce sensitive responses to various physical and chemical stimuli in the elastomer, which makes this composite material show broad application prospects in the biomedical field, such as the development of intelligent drug delivery systems, wearable medical devices, and precision diagnostic tools; these characteristics combined not only make this composite material perform well in traditional applications, but also open up new possibilities for its application in high-tech fields; in addition, the LMPA of the present application, the mixed material of graphene and silicone rubber generally has a lower processing temperature and better molding performance, is suitable for 3D printing and other additive manufacturing technologies, and can simplify the manufacturing process of complex structures; by regulating the temperature during 3D printing and controlling the viscosity of the mixed slurry during printing to adjust the support stability of the printed structure; for example, as shown in the figure, a hollow multi-channel tubular structure is achieved by direct writing printing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present application provides a graph showing the modulus shift of a PDMS composite material mixed with three different low melting point alloys at 30, 50, and 80°C.

[0033] Figure 2 The present application provides a capacitance variation curve of an elastomer under a compression percentage of 0-20%.

[0034] Figure 3 A hollow multi-channel tubular structure obtained by direct writing printing technology using the smart material of the present application. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only preferred embodiments, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise specified in the following examples, the raw materials used are all commercially available products.

[0037] Example 1

[0038] 1. Weigh 20 g of 47°C low melting point alloy (whose composition is Ga (metal gallium)-In (metal indium)-Sn (metal tin)-Pb (metal lead)) and dissolve it in 300 mL of boiling deionized water until it melts.

[0039] 2. Disperse the molten low melting point alloy into boiling deionized water to obtain suspension A.

[0040] 3. Cool suspension A in ice water and keep stirring until the temperature drops below the melting point of the alloy, then let it stand until it settles.

[0041] 4. Draw out the supernatant, add a small amount of anhydrous ethanol and centrifuge, then dry in an oven to obtain the desired low melting point alloy micron particles.

[0042] 5. Repeat the above four steps to obtain 30°C low melting point alloy micron particles.

[0043] 6. Repeat steps 1-4 to obtain 70°C low melting point alloy micron particles.

[0044] 7. Take 0.5g of the above-prepared 47°C low-melting point alloy micron particles, 0.5g of 30°C low-melting point alloy micron particles, 0.5g of 70°C low-melting point alloy micron particles and 0.1g of graphene and 0.1547g of PDMS SE1700 part A, stir and mix them to prepare a composite slurry B in which LMPA accounts for 39% of the total volume of the material, PDMS SE1700 part A accounts for 60% of the total volume of the material, and graphene accounts for 1% of the total volume of the material.

[0045] 8. Then, according to the mass ratio of PDMS SE1700 part A to PDMS SE1700 part B of 10:1, 0.01547 g of PDMS SE1700 part B was added to the composite slurry B prepared in the above step 7 to obtain composite slurry C, and then 3D printing was performed. 3D printing adopted direct writing printing technology, and the printing process temperature was 10°C to prevent the added low melting point alloy from melting due to the influence of the machine operating temperature, which added difficulty to the manufacturing process; the obtained model was placed in an oven for drying.

[0046] Specific details are as follows Figure 3 As shown in the figure, the hollow multi-channel tubular structure obtained by direct writing printing technology is shown. From the figure, it can be seen that the mixed material of LMPA, graphene and silicone rubber in this application usually has a lower processing temperature and better molding performance, which is suitable for 3D printing and other additive manufacturing technologies, and can simplify the manufacturing process of complex structures; by regulating the temperature during 3D printing, the viscosity of the mixed slurry during printing is controlled to adjust the support stability of the printed structure. For example, as shown in the figure, a hollow multi-channel tubular structure is realized by direct writing printing technology.

[0047] During the 3D printing process, the temperature is controlled at 10 degrees Celsius to prevent the added low-melting-point alloy from melting due to the influence of the machine's operating temperature, which would add difficulty to the manufacturing process. The printing process can control the viscosity of the mixed slurry at this temperature to avoid being affected by the melting of LMPA to achieve deposition molding.

[0048] As attached Figure 1 As shown, this is a graph showing the modulus changes of the PDMS composite material of this embodiment mixed with three different low melting point alloys at 30, 50, and 80°C. It can be seen from the accompanying figure that the modulus of the composite material of this example at 30, 50, and 80°C hardly changes over time, and it has excellent stability and can be used to manufacture materials with excellent shock absorption and cushioning properties, which are suitable for protective packaging and sports equipment.

[0049] As attached Figure 2 As shown, the capacitance change curve of the elastic body obtained in this example under the condition of 0-20% compression percentage; Figure 2 It can be seen that the elastic body of the present application has a sensing function, specifically through Figure 2 The change in capacitance is reflected in the figure. It can be seen from the figure that the composite material has excellent sensing function. This is because carbon nanotubes or graphene are deliberately introduced as functional fillers in the process of preparing the prepolymer slurry; these nano-scale materials have excellent electrical conductivity and mechanical properties, which can effectively enhance the conductivity and sensitivity of the composite material, so that the material can produce obvious electrical signal response when external stress, temperature or other environmental changes occur. This design strategy not only gives the composite material sensing function, but also improves its overall performance, laying a solid foundation for the development of smart materials and structures.

[0050] The stiffness of the material prepared in the examples of the present application varies in the range of 9-18 MPa.

[0051] Example 2

[0052] 1. Weigh 20 g of 47°C low melting point alloy (whose composition is Ga (metal gallium)-In (metal indium)-Sn (metal tin)-Pb (metal lead)) and dissolve it in 300 mL of boiling deionized water until it melts.

[0053] 2. Disperse the molten low melting point alloy into boiling deionized water to obtain suspension A.

[0054] 3. Cool suspension A in ice water and keep stirring until the temperature drops below the melting point of the alloy, then let it stand until it settles.

[0055] 4. Draw out the supernatant, add a small amount of anhydrous ethanol and centrifuge, then dry in an oven to obtain the desired low melting point alloy micron particles.

[0056] 5. Repeat the above four steps 1-4 to obtain 30°C low melting point alloy micron particles.

[0057] 6. Repeat steps 1-4 to obtain 70°C low melting point alloy micron particles.

[0058] 7. Take 0.5g of the above-mentioned 47°C low-melting point alloy micron particles, 0.5g of 30°C low-melting point alloy micron particles, 0.5g of 70°C low-melting point alloy micron particles and 0.1g of carbon nanotubes and 0.1547g of PDMS SE1700 part A, stir and mix them to prepare a composite slurry B in which LMPA accounts for 39% of the total volume fraction of the material, PDMS SE1700 part A accounts for 60% of the total volume fraction of the material, and carbon nanotubes account for 1% of the volume fraction of the material.

[0059] According to the mass ratio of PDMS SE1700 part A to PDMS SE1700 part B of 10:1, 0.01547 g of PDMS SE1700 part B was added to the composite slurry B to obtain composite slurry C, which can be 3D printed, and the obtained model is placed in an oven for drying; the subsequent 3D printing process is the same as the above embodiment 1.

[0060] Example 3

[0061] 1. Weigh 10 g of 47°C low melting point alloy (Ga (metal gallium)-In (metal indium)-Sn (metal tin)-Bi (metal bismuth)) and dissolve it in 300 mL of boiling deionized water until it melts.

[0062] 2. Disperse the molten low melting point alloy into boiling deionized water to obtain suspension A.

[0063] 3. Cool suspension A in ice water and keep stirring until the temperature drops below the melting point of the alloy, then let it stand until it settles.

[0064] 4. Draw out the supernatant, add a small amount of anhydrous ethanol and centrifuge, then dry in an oven to obtain the desired low melting point alloy micron particles.

[0065] 5. Repeat the above four steps 1-4 to obtain 30°C low melting point alloy micron particles.

[0066] 6. Repeat steps 1-4 to obtain 70°C low melting point alloy micron particles.

[0067] 7. Take 0.3g of the above-mentioned 47°C low-melting point alloy micron particles, 0.3g of 30°C low-melting point alloy micron particles, 0.3g of 70°C low-melting point alloy micron particles and 0.1g of graphene and 0.1547g of Ecoflex 00-30A, stir and mix them to prepare a composite slurry B with a total volume fraction of LMPA of 25% and a volume fraction of graphene of 2%.

[0068] According to the mass ratio of Ecoflex 00-30A part to Ecoflex 00-30B part of 10:1, 0.01547g of Ecoflex 00-30B part was added to the composite slurry B to obtain composite slurry C, which can be 3D printed, and the obtained model is placed in an oven for drying; the subsequent 3D printing process is the same as the above embodiment 1.

[0069] Comparative Example 1

[0070] (1) Weigh 20 g of a 47°C low melting point alloy (whose components are indium, bismuth, tin, lead and cadmium) and dissolve it in 300 mL of boiling deionized water until it melts.

[0071] (2) The molten low melting point alloy is dispersed in boiling deionized water to obtain a suspension A.

[0072] (3) Cool suspension A in ice water while stirring until the temperature drops below the melting point of the alloy and allow to settle.

[0073] (4) Extract the supernatant, add a small amount of anhydrous ethanol, centrifuge, and dry in an oven to obtain the desired low melting point alloy micron particles.

[0074] (5) Repeat the above four steps to obtain 30°C low melting point alloy micron particles.

[0075] (6) Repeat steps (1) to (4) to obtain 70°C low melting point alloy micron particles.

[0076] (7) 0.5 g of the above-mentioned 47°C low-melting point alloy micron particles, 0.5 g of the 30°C low-melting point alloy micron particles and 0.5 g of the 70°C low-melting point alloy micron particles were mixed with 0.1438 g of PDMS SE1700 part A to prepare a composite slurry B in which the volume fraction of the low-melting point alloy micron particles was 60%.

[0077] (8) According to the mass ratio of PDMS SE1700 part A to part B of 10:1, 0.01438 g of PDMS SE1700 part B was added to the composite slurry B to obtain composite slurry C for 3D printing.

[0078] (9) The obtained model is placed in an oven for drying.

[0079] The smart slurry exhibits shear thinning at a shear rate of 1s-1 to 100s-1 and viscoelastic inversion at a shear pressure of 1Pa to 10000Pa. As the temperature increases, the elastic modulus of the smart slurry decreases significantly in two places.

[0080] The stiffness of the material prepared in this comparative example varies in the range of 5-7 MPa.

Claims

1. A smart material, characterized in that: The main components of the material include a dispersed phase accounting for 20-40% of the total volume of the material, a dispersed medium accounting for 50-70% and a functional filler accounting for 1-6%. The dispersed phase and the functional material are uniformly dispersed in the dispersed medium. The dispersed phase includes low-melting-point alloy particles, and the dispersed medium includes an elastomer prepolymer; the functional filler is a carbon nanotube or graphene.

2. The smart material according to claim 1, characterized in that: The main components of the material include 23-35% of the dispersed phase, 55-65% of the dispersed medium and 1-5% of the functional filler, which accounts for 23-35% of the total volume of the material.

3. The smart material according to claim 1, characterized in that: The low melting point alloy is a mixture of different types of low melting point alloys, and the specific low melting point alloy includes one or more of Ga, Ga-In-Sn-Bi, and Ga-In-Sn-Pb; the elastomer prepolymer includes any one of PDMS SE1700, PDMS184, Ecoflex 00-30, and Ecoflex 00-50, or a combination of two or more thereof.

4. The smart material according to claim 1, characterized in that: The melting point of the low-melting-point alloy particles is lower than 200°C.

5. The smart material according to claim 4, characterized in that: The melting point of the low-melting-point alloy particles is 30-70°C.

6. A method for preparing the smart material according to any one of claims 1 to 5, characterized in that: It includes: The low melting point alloy particles, functional fillers and elastomer prepolymers are uniformly mixed to prepare smart material slurry, which is then solidified to obtain smart materials.

7. The method for preparing the smart material according to claim 6, characterized in that: The preparation method specifically comprises: (1) providing a first mixed system comprising low melting point alloy particles, a functional filler and a first prepolymer component; (2) Adding a second prepolymer component to the first mixed system, and then stirring and mixing to form a second mixed system, to obtain a 3D printable smart material slurry, and then curing to obtain a smart material elastomer.

8. The method for preparing the smart material according to claim 7, characterized in that: The first prepolymer component is the elastomer prepolymer, and the second prepolymer component is the elastomer prepolymer; in the 3D printing, the temperature of the printing process is not higher than 10°C.

9. Application of the smart material according to any one of claims 1 to 5 in the field of 3D printing.

10. The use according to claim 9, characterized in that: The products of the applications mentioned include the development of smart drug delivery systems, wearable medical devices, and precision diagnostic tools.

Citation Information

Patent Citations

  • Low-melting-point alloy with melting point being 40-60 DEG C and preparation method of low-melting-point alloy

    CN105349866A

  • Modified polysiloxane and application thereof

    CN110218329A

  • Multi-stable-state variable-rigidity intelligent material as well as preparation method and application thereof

    CN113831736A

  • Preparation method and application of polymer sponge sensing material based on rigid-flexible double-component conductive filler

    CN115260569A